Interpersonal Communication Attribution of Prisoner Companion (PRICO) Hygiene at the State Detention Center Class I Depok - Afriyansyah, Ari; Marlinda Irwanti (The Eastasouth Journal of Social Science and Humanities, 2025)
The complexity of the problems that occur in Rumah Tahanan Negara (Rutan) Kelas I Depok, is one of the problems that continues. The relationship between officers and tahanan pendamping (tamping) that looks good, becomes a false picture with the discovery of communication devices in the prison cells, plans to smuggle narcotics into the prison environment, and conflicts in communication between prisoners and prisoners. The hidden motive behind the behavior and interpersonal communication that is well established between officers and companions, is an aspect that needs to be explored. This research, focuses on aspects of interpersonal communication and attribution in tamping. This research uses a post-positivisme paradigm with a descriptive qualitative method, which refers to the theory of interpersonal communication and attribution with the Coding Color Analysis Procedure (CCAP) analysis method. Data collection was carried out by means of observation, interviews and literature documents. The results of this research see a more intense interpersonal communication process between tamping and officers outside of duty hours with the context of the conversation more about personal life. Internal attribution of tamping different behavior, will be good with officers and will be conflict if with other prisoners. The tamping motive of getting benefits and convenience from closeness to officers is one of the causes of differences in internal attribution of tamping behavior.